Changes in the Physical Properties of Precipitation in Pine Stands in the Area with A Low Degree of Air Pollution (Western Pomerania) - Kruszyk, Robert (Quaestiones Geographicae, 2013)
The study presents the results of research conducted in the years 2010-2012 in pine stands in Western Pomerania. The research included physicochemical properties of bulk precipitation and throughfall. The results confirm that despite a decrease in the total throughfall in the interception process, the size of mineral and organic depositions in pine stands exceeded values recorded for bulk precipitation. It was caused both by the process of enriching the throughfall with (K+, Mg2+) rinsed out of needles and leaves and by washing off the dry deposition (NH4+, Cl-, Na+, SO42-, NO3 -). The share of leaching processes for K+ was 74.1%, while for Mg2+ 23.6% of the total load of these elements brought to the ground with throughfall. In the case of Ca2+ no canopy leaching was observed for this element. The throughfall acidification processes were mostly caused by NO3-.